1866 Utah Acts 51, ch. 22, tit. 2, § 8 - (:unkn) unknown (My University, 1865)
Whoever fights a duel with deadly weapons, and inflicts a mortal wound on his antagonist, wherefrom death ensues, is guilty of murder of the first degree, and shall be punished accordingly."
Keywords: DUELING